Implementation of Work Motivation on the Quality of Public Services at The Bangkala Village Office, Maiwa District, Enrekang Regency - A. Marsal Husain; Kamaruddin Sellang; Andi Astinah Adnan (MultiTech Publisher, 2024)
This study focuses on the